ADOPTION OF SMART TECHNOLOGIES THROUGHT THE TRANSITION TO A NEW ERP SYSTEM WITHIN INDUSTRY 4.0 - TĂNASE ANDREEA GABRIELA; NECULA ADINA-THEODORA; MĂLDĂREANU ANDREEA; CREȚU RALUCA-FLORENTINA; BANȚA VIOREL COSTIN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This article for which this case study was conducted, provide a broad analysis of the factors that led the company to embrace the benefits by using smart technologies such as AI (Artificial Intelligence), RPA (Robotic Process Automation), and even ML (Machine learning), all integrated in a cloud platform into their existing IT solutions, whether we are reffering to legacy systems or the new ERP system (Enterprise Resources Planning), in this case, discussing about SAP. The case study covered everything from the modelled economic processes, adopted technologies, used software and hardware platforms, and why to adopt a solution based on “cloud” instead of “on-premise” solution. The research methods and techniques used for this analysis is called interventionist research (IVR) or, not far away, quantitative methods such as correlational research. The authors of this scientific article wanted an analysis of the impact on the work performed by employees through the implementation of new solutions..